Traditions of Remo in Blater Community of Madura - Dinara M. Julijanti; Myrtati Dyah Artaria; Yayan S. Suryandaru; Sharyn G. Davies (MOZAIK HUMANIORA, 2021)
Blater community is a sub-culture within the Madurese community, which until now still exists in carrying out Remo tradition. Members of blater have various professions and activities, and they are feared and respected by the people of West Madura. They maintain their influence through a gathering called Remo in the cities of Bangkalan and Sampang. During Remo, blater members conduct saweran or bhubuwan (giving some money) to the host. The amount varies from around 500.000 to 2.000.000 rupiahs per person according to the financial and social status of the member. This is a qualitative research. The data collection techniques were in-depth interview, observation, and documentation. We interviewed the members of blater, and analyzed the qualitative data. We conclude that every community needs activities to maintain its existence. In West Madura society, it comes in the form of Remo. This existence is required as a form of recognition from the society. The study also finds that it is important for the individual member to assure oneself of having power of symbolic, social, cultural, and economic capital.